STRATEGI GURU DALAM MENINGKATKAN MINAT BELAJAR DAN MEMBANGUN KARAKTER PESERTA DIDIK (Studi Kasus Di SMPN 23 Tulang Bawang Barat) - Ahmad Riva’i; Pondra Muliawan; Ubaidillah (STKIP Subang, 2025)
This study aims to describe teacher strategies for increasing student interest in learning and developing character in Islamic Religious Education (PAI) at SMPN 23 Tulang Bawang Barat. This study employed a qualitative descriptive approach, with data collection techniques including observation, interviews, and questionnaires. This approach was used to obtain an in-depth understanding of the learning process and the strategies teachers employ in PAI learning activities. The results of the study indicate that students' learning interest is quite high, as indicated by a sense of enjoyment in the lessons, readiness to learn, and active participation in the learning process. However, several obstacles were still encountered, such as boredom due to monotonous learning methods and a lack of enthusiasm for learning in some students. In terms of character, students generally demonstrate good character, especially in aspects of honesty, responsibility, politeness, social awareness, and discipline in worship, although there are still some students who require further guidance. Teacher strategies in increasing students' interest in learning and building their character include the application of varied learning methods, such as lectures, discussions, stories, and assignments, the use of visual learning media, providing motivation and praise, instilling character values ​​through group prayer, and teacher role models in attitudes and actions. The conclusion of this study shows that creative, varied, and role model-oriented Islamic Religious Education (PAI) teacher learning strategies have proven effective in increasing students' interest in learning while shaping their character, so they can be a reference for teachers and schools in improving the quality of Islamic Religious Education (PAI) learning sustainably.